Yitae Scholasticae. The Yournal of Educational Biography, Tom 17, 1998, nr 2 - Hellwig, Jan (Biuletyn Historii Wychowania, 1999)
Yitae Scholasticae. The Yournal of Educational Biography, Tom 17, 1998, nr 2